2021
DOI: 10.3390/brainsci11030323
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Representation of Thalamic Projection Neurons within Prefrontal-Thalamic-Hippocampal Circuitry in a Rat Model of Third Trimester Binge Drinking

Abstract: Alcohol exposure (AE) during the third trimester of pregnancy—a period known as the brain growth spurt (BGS)—could result in a diagnosis of a fetal alcohol spectrum disorder (FASD), a hallmark of which is impaired executive functioning (EF). Coordinated activity between prefrontal cortex and hippocampus is necessary for EF and thalamic nucleus reuniens (Re), which is required for prefrontal-hippocampal coordination, is damaged following high-dose AE during the BGS. The current experiment utilized high-dose AE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…There was no significant main effect of sex on Re volume, as well as no significant interaction between postnatal treatment and sex. Upon investigation of group means, AE reduced Re volume, which is similar to previous findings from our lab ( Gursky et al, 2019 ; Gursky and Klintsova, 2021 , 2022 ). These data are represented in Figure 2A .…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…There was no significant main effect of sex on Re volume, as well as no significant interaction between postnatal treatment and sex. Upon investigation of group means, AE reduced Re volume, which is similar to previous findings from our lab ( Gursky et al, 2019 ; Gursky and Klintsova, 2021 , 2022 ). These data are represented in Figure 2A .…”
Section: Resultssupporting
confidence: 90%
“…Previous work from our lab has established that AE brings on immediate death of neurons in Re that lasts long into adulthood ( Gursky et al, 2020b ). However, we have also demonstrated that AE leads to an increase in proportion of Re neurons that collaterally project to both mPFC and HPC without altering the number of neurons that project to only one of these two structures ( Gursky and Klintsova, 2021 ). Thus, AE may be creating an imbalance of excitatory neurons in the Re that could ultimately affect the anatomical substrates of the mPFC-Re-HPC circuit (i.e., mPFC axonal projections).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations